2011
DOI: 10.1007/s10815-011-9583-z
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the impact of IVF and ICSI on major malformations after adjusting for the effect of subfertility

Abstract: Objective To estimate the effect of assisted reproductive technology (ART) on major malformation (MM) rate in ART offspring independent of the effect of subfertility on MM. Design Meta-analysis. Methods This meta-analysis is based on our previously published meta-analysis of observational studies evaluating the relationship between ART treatment and MM rates, as well as recent research by Zhu et al. to estimate the impact of subfertility alone on MM in subfertile couples conceiving spontaneously. Results The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 44 publications
(46 reference statements)
2
63
0
5
Order By: Relevance
“…The results obtained in this study confirm the concept proposed by many researchers that infertility, with or without ART, is a condition leading to increased risk of birth defects [28][29][30][31]. Several studies have indicated that ART is associated with a significantly higher risk of congenital defects in newborns when compared to spontaneous conception [32].…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained in this study confirm the concept proposed by many researchers that infertility, with or without ART, is a condition leading to increased risk of birth defects [28][29][30][31]. Several studies have indicated that ART is associated with a significantly higher risk of congenital defects in newborns when compared to spontaneous conception [32].…”
Section: Discussionsupporting
confidence: 90%
“…We would like to raise some concerns about the methods used to 'adjust' for the effect of subfertility in the metaanalysis of ART and major birth defects in the recent paper by Rimm et al [1] Having also published a systematic review and meta-analysis of ART and birth defects (BDs) [2], we are concerned both by the methods used and some of the statements made in the Rimm et al paper.…”
Section: To the Editormentioning
confidence: 99%
“…In their recent meta-analysis, Rimm et al [1] attempt to 'adjust' the study-specific estimates of BD risk for couples conceiving by ART for the proportion they estimate to be due to underlying subfertility, by subtracting the risk for couples who conceived naturally after more than 12 months (based on Zhu et al [3]). In doing so, they have assumed that the underlying causes of infertility in couples who managed to conceive spontaneously after 12+ months of trying were the same (and of equal severity) as those in couples who required ART to conceive.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, infertility is associated with abnormal sperm parameters and in turn men with azospermia or oligospermia have constitutional chromosomal abnormalities that may contribute to the development of birth defects [8,9]. Along this line, the frequency of birth defects has been shown to be increased among women who conceived spontaneously after a history of infertility [10,11,3,4].…”
Section: Introductionmentioning
confidence: 99%